Rare bird documentation form for Bohemian Waxwing at MacLean Hall at University of Iowa, 1976 - DeCoster, R. J. (Richard Joseph)et al (1976)
Rare bird documentation form for a Bohemian Waxwing at MacLean Hall at University of Iowa in Johnson County, IA on February 1, 1976. Epson - sheet feed